PENGARUH PENERAPAN METODE DEMONSTRASI TERHADAP HASIL BELAJAR PESERTA DIDIK MUATAN IPA KELAS IV DI SDN 102/II SUNGAI KERJAN - Michella Asfinivia (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2022)
This examination is awakened by low learning outcomes of science content that has not yett reached the minimum completeness criteria (KKM). One variable that contributes is the low learning outcomes of practice, especially in science learning. Therefore, the right learning strategy is needed which affects the results of easy-to-understand learning. The aim in this study was to understand how much impact the demontrasion method on the results of learning in class IV at SDN 102 / II Kerjan River in Science learning. This type of research is a type of Pre Experimental Design research with a quantitative methodology. Design that uses the type of One Group Pretest Posttest Design. The subjects of this study were 27 students at SD Negeri 102/II Sungai Kerjan. In this examination, the data collection instrument of the researcher used an instrument in the form of test questions. The data collection technique utilizes up to 20 pretest and posttest questions. The data analysis technique used a statistical test, namely the Paired Samples T-Test test because the data were normally distributed. Information handled using SPSS 22.